Subphrenic Lymph Node Metastasis Predicts Poorer Prognosis for Nasopharyngeal Carcinoma Patients With Metachronous Metastasis - Zhang, Xue-Fang; Zhang, Yan; Liang, Xu-Wei; Chen, Jia-Luo; Zhi, Sheng-Fang; Yin, Wen-Jing; Wang, Meng-Yao; Dong, En-Lai; Chen, Dong-Ping (Frontiers in Oncology, 2021)
Aim We retrospectively analyzed the distribution of distant lymph node metastasis and its impact on prognosis in patients with metastatic NPC after treatment. Methods From 2010 to 2016, 219 NPC patients out of 1,601 (182 from the Affiliated Cancer Hospital and Institute of Guangzhou Medical University, and 37 from the Affiliated Dongguan Hospital, Southern Medical University) developed distant metastasis after primary radiation therapy. Metastatic lesions were divided into groups according to location: bones above the diaphragm (supraphrenic bone, SUP-B); bones below the diaphragm (subphrenic bone, SUB-B); distant lymph nodes above the diaphragm (supraphrenic distant lymph nodes, SUP-DLN); distant lymph nodes below the diaphragm (subphrenic distant lymph nodes, SUB-DLN), liver, lung, and other lesions beyond bone/lung/distant lymph node above the diaphragm (supraphrenic other lesions, SUP-OL); other lesions beyond bone/liver/distant lymph node below the diaphragm (subphrenic other lesions, SUB-OL); the subtotal above the diaphragm (supraphrenic total lesions, SUP-TL); and the subtotal below the diaphragm (subphrenic total lesions, SUB-TL). Kaplan–Meier methods were used to estimate the probability of patients’ overall survival (OS). Univariate and multivariate analyses were applied using the Cox proportional hazard model to explore prediction factors of OS. Results The most frequent metastatic locations were bone (45.2%), lung (40.6%), liver (32.0%), and distant lymph nodes (20.1%). The total number of distant lymph node metastasis was 44, of which 22 (10.0%) were above the diaphragm, 18 (8.2%) were below the diaphragm, and 4 (1.8%) were both above and below the diaphragm. Age (HR: 1.02, 95% CI: 1.00, 1.03, p = 0.012), N stage (HR: 1.26, 95% CI: 1.04, 1.54, p = 0.019), number of metastatic locations (HR: 1.39, 95% CI: 1.12, 1.73, p = 0.003), bone (HR: 1.65, 95% CI: 1.20, 2.25, p = 0.002), SUB-B (HR: 1.51, 95% CI: 1.07, 2.12, p = 0.019), SUB-DLN (HR: 1.72, 95% CI: 1.03, 2.86, p = 0.038), and SUB-O L(HR: 4.46, 95% CI: 1.39, 14.3, p = 0.012) were associated with OS. Multivariate analyses revealed that a higher N stage (HR: 1.23, 95% CI: 1.00, 1.50, p = 0.048), SUB-DLN (HR: 1.72, 95% CI: 1.02, 2.90, p = 0.043), and SUB-OL (HR: 3.72, 95% CI: 1.14, 12.16, p = 0.029) were associated with worse OS. Conclusion Subphrenic lymph node metastasis predicts poorer prognosis for NPC patients with metachronous metastasis; however, this needs validation by large prospective studies.